2016
DOI: 10.1017/s0021859615001331
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variations in the soluble starch synthase II gene family result in changes of grain quality and starch properties in rice (Oryza sativa L.)

Abstract: SUMMARYSoluble starch synthase II (SSII) plays an important role in the biosynthesis of starch and in rice it consists of three isoforms encoded by SSII-1, SSII-2 and SSII-3. However, the genetic effects of various SSII alleles on grain quality have not been systematically characterized. In the present study, the japonica alleles on SSII-1, SSII-2 and SSII-3 (SSIIa) loci from a japonica cultivar, Suyunuo, were respectively introgressed by molecular marker-assisted selection into a typical indica cultivar, Guic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…This type of inconsistency suggested that compared to Waxy and SSIIa genes, these markers may have minor or environment-dependent effects on starch traits. For further evaluation of their roles in determining starch characteristics, constructing near-isogenic-lines could be a suitable approach, as demonstrated in recent reports (Luo et al, 2015; Fan et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of inconsistency suggested that compared to Waxy and SSIIa genes, these markers may have minor or environment-dependent effects on starch traits. For further evaluation of their roles in determining starch characteristics, constructing near-isogenic-lines could be a suitable approach, as demonstrated in recent reports (Luo et al, 2015; Fan et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fan et al (2017) also detected the effect of SSIIa gene on AAC and viscosity parameters using near-isogenic lines. Thus, the effect of SSIIa gene on AAC-related traits could not be purely attributed to gene linkage effect although the SSIIa GC SNPs were found associated with the G SNP of intron 1 in Waxy gene in most cases in this study (103 out of 137, 75.2% percent).…”
Section: Discussionmentioning
confidence: 99%
“…Rice is one of the most important crops, and provides the staple food for over half the world's population. Starch is the main component of rice endosperm, and its properties greatly influence the eating and cooking qualities of rice and its processing method in industrial use [1][2][3]. Therefore, the cultivation of rice varieties with different starch properties is one of the important goals in rice breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Starch biosynthetic genes played important roles for starch properties in a RIL population which was originated from the cross, IR64/Nipponbare (Luo et al 2015). Allelic variation in the soluble starch synthase II gene family is important for grain quality and starch properties (Fan et al 2017). In addition, genes that encode for rice starch branching enzyme IIb were identified through MutMapPlus (Nakata et al 2017).…”
Section: Introductionmentioning
confidence: 99%